2018
DOI: 10.1177/0893318918783612
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Tie: Creating Exchange Relationships That Encourage Employee Advocacy as an Organizational Citizenship Behavior

Abstract: This study investigates the communication elements within organizations that enhance social exchanges and influence an individual's willingness to spread positive information about their employer. Findings from a survey of employees in a United States-based health care organization (N = 223) indicate that organizational commitment mediates the relationship between employee-centered internal communication by organizations and employee advocacy. Employees with strong organizational commitment perceive that their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 43 publications
(92 reference statements)
0
40
0
13
Order By: Relevance
“…Kim and Rhee (2011) similarly coined the term, positive megaphoning, referring to employees' voluntary information sharing behaviors with people in their personal network such as friends or family members. Previous works have suggested that a favorable organization-employee relationship, organizations' symmetrical communication practices or authentic behaviors, organizational commitment and leadership can particularly increase employees' likelihood of advocating for their organizations (Kim and Rhee, 2011;Lee and Kim, 2017;Lee et al, 2018;Walden and Westerman, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kim and Rhee (2011) similarly coined the term, positive megaphoning, referring to employees' voluntary information sharing behaviors with people in their personal network such as friends or family members. Previous works have suggested that a favorable organization-employee relationship, organizations' symmetrical communication practices or authentic behaviors, organizational commitment and leadership can particularly increase employees' likelihood of advocating for their organizations (Kim and Rhee, 2011;Lee and Kim, 2017;Lee et al, 2018;Walden and Westerman, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous researchers noted that the concept is characterized by individuals' positive word-of-mouth (WOM) behaviors that recommend or support their organization as well as the products and services (Tsarenko et al , 2018) to external publics such as friends or family members (Bettencourt and Brown, 2003; Fullerton, 2011) or potential employees (Schweitzer and Lyons, 2008) to seek reputation benefits for their organizations (Seiling, 2008). Several scholars have further argued that employee advocacy, as an external, boundary-spanning role (Tsarenko et al , 2018; Vlachos et al , 2017), is not limited to positive WOM but also includes defending a company when it is attacked by external forces (Walden and Kingsley Westerman, 2018), defining it as employees' voluntary promotion or defense of a company, brands and its products externally (Men, 2014). Kim and Rhee (2011) similarly captured the concept of the positive megaphoning of employees, referring to their intention to share positive information about their company externally to people around them (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social exchange theory atau teori pertukaran sosial digunakan para peneliti organisasi sebagai kerangka yang memiliki pengaruh untuk menjelaskan perilaku kerja seseorang (Cropanzano et al, 2017). Kegiatan tukarmenukar tersebut dapat memperkuat hubungan antar pihak yang terlibat dalam hubungan pertukaran, yang pada akhirnya menghasilkan perilaku yang produktif (Walden et al, 2018). Seseorang dalam hubungan pertukaran dengan orang lain akan mengharapkan imbalan yang diterima oleh setiap pihak sesuai dengan pengorbanan yang telah di keluarkannya, makin tinggi pengorbanan, makin tinggi keuntungan yang diterima oleh setiap pihak.…”
Section: Pendahuluanunclassified